Chloramphenicol Selection of IS10 Transposition in the cat Promoter Region of Widely Used Cloning Vectors. - Coral González-Prieto; Leticia Agúndez; Matxalen Llosa (PLoS ONE, 2015)
The widely used pSU8 family of cloning vectors is based on a p15A replicon and a chloramphenicol acetyltransferase (cat) gene conferring chloramphenicol resistance. We frequently observed an increase in the size of plasmids derived from these vectors. Analysis of the bigger molecular species shows that they have an IS10 copy inserted at a specific site between the promoter and the cat open reading frame. Promoter activity from both ends of IS10 has been reported, suggesting that the insertion events could lead to higher CAT production. Insertions were observed in certain constructions containing inserts that could lead to plasmid instability. To test the possibility that IS10 insertions were selected as a response to chloramphenicol selection, we have grown these constructs in the presence of different amounts of antibiotic and we observed that insertions arise promptly under higher chloramphenicol selective pressure. IS10 is present in many E. coli laboratory strains, so the possibility of insertion in constructions involving cat-containing vectors should be taken into account. Using lower chloramphenicol concentrations could solve this problem.